Acidic heat-sensitive resin and pre-coated resin copper foil
Through the pre-coated resin copper foil technology of acidic thermosensitive resin and copper foil, combined with inorganic nanofillers and epoxy resins, the problems of low efficiency in the preparation of fine circuit boards and high thermal expansion coefficient of dielectric materials in the prior art are solved, and the low Dielectric constant and efficient preparation of fine PCB boards.
Patent Information
- Application Number
- CN202311751477.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-12-19
AI Technical Summary
In the preparation of micron-level fine circuits and multi-layer PCB boards, the mechanical processing and laser ablation efficiency are low, and the high thermal expansion coefficient and high dielectric constant of organic resin dielectric materials lead to delays and losses in electromagnetic signal transmission, which is difficult to meet. High-speed and high-frequency applications.
Pre-coated resin copper foil consisting of acidic thermosensitive resin and copper foil, a coating with low dielectric constant and low thermal expansion coefficient is formed through chemical etching and thermal curing, and combined with inorganic nanofillers and epoxy resins to achieve efficient preparation of fine PCBs. Multi-layer circuit board.
The coating with low dielectric constant, low thermal expansion coefficient and excellent heat resistance is achieved, which improves the preparation efficiency and accuracy, and is suitable for the manufacturing of micro-nano circuits and multi-layer precision circuit boards.
Smart Images

Figure CN118048020B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PCB board preparation, and particularly relates to an acidic heat-sensitive resin, and also relates to an alkaline water-soluble pre-coated resin copper foil with a copper foil carrier and a protective film. Background Art
[0002] Printed circuit board (PCB) is a collection of resin substrate and conductive circuit. With the miniaturization and high frequency of electronic devices, the scale of electronic circuits and interlayer conductive holes of multilayer PCB tends to be refined, especially the IC carrier of integrated circuit (IC) chip, and the pattern etching requires more refinement. Multilayer fine PCB board is to deposit copper layer on the carrier, etch out circuit, then bond resin layer, deposit copper layer, and repeat this process continuously. These preparation processes require higher production and processing efficiency. Rigid multilayer precision printed circuit board and IC carrier are mainly prepared with heat-crosslinked resin film or sheet, such as organic dielectric insulating materials such as ABF, prepreg and BT resin sheet. The circuit on the carrier and the connection between the circuits of each layer are made by mechanical processing (cutting, drilling), or laser ablation. The preparation process is precise and complicated, but mechanical processing is not only limited in precision, but also as inefficient as laser ablation. Therefore, more efficient methods and materials are needed to prepare micron-level fine circuits and through holes and processing methods involved in multilayer PCB boards.
[0003] Organic resin is a type of dielectric material that generates parasitic capacitance under the action of an electric field, resulting in transmission delay and loss. The transmission delay and loss of electromagnetic signals are related to the dielectric constant D of the dielectric material. k The square root of The propagation rate is proportional to The influence becomes more serious with the increase of electromagnetic wave frequency. For high-speed PCB, such as IC substrate and high-frequency and ultra-high-frequency applications, a lower dielectric constant D is required. k And the loss factor D f The dielectric material is used as the substrate layer.
[0004] The difference in the coefficient of thermal expansion (CTE) between the resin and the conductive material of the IC substrate should be as small as possible to reduce the thermal stress between the conductive material and the substrate caused by temperature changes. The CTE of organic resin materials is usually higher than 60ppm, which is several times higher than the CTE of copper. The coefficient of thermal expansion of the dielectric insulation material used to prepare the IC substrate needs to be reduced. Summary of the invention
[0005] In view of this, the present invention provides an acidic thermosensitive resin, whose thermosetting product has excellent dielectric properties and a low thermal expansion coefficient, and a pre-coated resin copper foil (Pre-Coated Cooper Foil, hereinafter referred to as PCCF) that can be etched by alkaline aqueous solution, which is composed of the composition and copper foil; chemical etching and multi-layer stacking of the pre-coated resin copper foil can efficiently prepare fine PCB multi-layer circuit boards.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:
[0007] An acidic heat-sensitive resin comprises the following components:
[0008] A: acidic resin, 15-60 parts by weight, preferably 20-50 parts by weight;
[0009] B: epoxy resin, 10-50 parts by weight, preferably 15-45 parts by weight;
[0010] C: low dielectric constant inorganic nanofiller, 25-55 parts by weight, preferably 30-50 parts by weight;
[0011] The total weight of components AC is 100 parts by weight;
[0012] In addition, it also includes D: epoxy thermal curing catalyst, the amount of the epoxy thermal curing catalyst is 0.1-5%, preferably 0.2-1% of the total weight of components AC.
[0013] An acidic thermosensitive resin composed of a fluorine-containing rigid resin A containing carboxyl (-COOH), an epoxy resin B), an inorganic nanofiller with a low dielectric constant C) and an epoxy thermal curing catalyst D) is coated on a conductive metal foil to form a resin-coated metal film / sheet. The coated metal film / sheet can be aqueously etched to form a pattern of conductive paths or micropores, and then thermally cured to form a rigid composite material layer of the coating-metal foil; the cured organic dielectric coating has a low dielectric constant, a relatively low CTE and excellent heat resistance. The pre-coated resin copper foil can be aqueously etched to prepare micro-nano circuits and multi-layer precision circuit boards.
[0014] In the component A, the acidic resin includes a fluorine-containing acidic resin a1 prepared from a fluorine-containing alcohol or a fluorine-containing phenol having a fluorine mass ratio greater than 30% as a raw material, and the acid equivalent value V of the acidic resin excluding the solvent is a Greater than 180 g / mol, preferably 190-400 g / mol, the mass ratio of fluorine in component A is greater than 20%.
[0015] Specific fluorinated alcohols or fluorinated phenols are shown as FA, F-FB, FBm, and FBp:
[0016]
[0017] The fluorine mass ratio of these fluorinated alcohols / phenols ranges from the lowest fluorine content of about 36% in hexafluorobisphenol A (FA) to about 58% in fluorophenylbis(hexafluoroisopropanol) (F-FB); the dielectric constant D k Low, for example, polytetrafluoroethylene fluorocarbon resin (PTFE) has a very low D k , can be used for D k The PCB board has extremely high requirements, but the surface energy of PTFE is low, and the adhesion to the conductive material is weak. At the same time, PTFE does not contain acidic functional groups and cannot be chemically etched with aqueous reagents. Fluorinated long-chain alkane compounds are often used to reduce the dielectric constant of the material, but they have low Tg, insufficient mechanical strength and heat resistance. The preparation of acidic resin with rigid fluorinated alcohol / phenol can take into account the high Tg, heat resistance, rigidity and low dielectric constant requirements of PCB substrate materials.
[0018] Fluorine-containing acidic resin a1 is obtained by reacting fluorine-containing alcohol / phenol with acid anhydride. Suitable acid anhydrides include dibasic acid and tribasic or tetrabasic acid anhydride, which can be aromatic or alicyclic acid anhydride, such as phthalic anhydride, (methyl) tetrahydrophthalic anhydride, (methyl) hexahydrophthalic anhydride, (methyl) diacyl anhydride, maleic anhydride, itaconic anhydride, succinic anhydride, trimellitic anhydride, pyromellitic dianhydride, diphenyl ether tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, succinic dianhydride, cyclohexyl tetracarboxylic dianhydride, etc. The acid equivalent value of the fluorine-containing acidic resin prepared with dibasic acid anhydride is higher than that of the tribasic or tetracarboxylic anhydride; the fluorine content of the fluorine-containing acidic resin prepared with an acid anhydride with a high molecular weight is low. The acid equivalent value refers to the mass of the resin corresponding to each mol of carboxyl group. The higher the acid equivalent value, the lower the carboxyl concentration. For example, a resin containing 1 mol of fluorine alcohol F-FB with a fluorine content of about 58% by mass is reacted with 1 mol of phthalic anhydride and 1 mol of trimellitic anhydride, and the resulting acidic resin has a fluorine content of about 31% and an acid equivalent value of about 250g / mol; if 1 mol of fluorine alcohol F-FB is reacted with 2 mol of phthalic anhydride, the resulting acidic resin has a fluorine content of about 34% and an acid equivalent value of about 370g / mol. Therefore, the acid equivalent value and fluorine content of the fluorine-containing acidic resin can be adjusted by combining acid anhydrides of different types and molecular weights. The higher the fluorine content, the lower the dielectric number of the resin. It is better that the fluorine content of the fluorine-containing acidic resin accounts for more than 20% of the mass of the acidic thermosensitive resin excluding the solvent, and the best acid equivalent value is 190-400g / mol. If the acid value is lower or higher than this range, the acidity of the resin will be too high or too low, the developability will be poor, and it will be unfavorable for etching fine patterns. The acid equivalent value is determined by titration with a standard alkali solution. The resin may first be made into a solution with an appropriate solvent. The fluorine content can be determined by elemental analysis.
[0019] The reaction of fluorinated alcohol / phenol with anhydride can refer to the public data and methods, add appropriate catalyst, stir the reaction at 60-100°C for several hours, and generally need to add an appropriate amount of solvent. Although organic solvents without acid or amine can be used, ether solvents with a boiling point of 60-180°C, preferably 60-130°C, such as tetrahydrofuran (THF), dipropyl ether, dibutyl ether; ketone solvents such as acetone, butanone, cyclohexanone, etc.; ester solvents such as butyl acetate, dimethyl carbonate, dibutyl carbonate, etc.; aromatic hydrocarbon solvents such as benzene, toluene, xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, etc. can also be used; for environmental protection and health considerations, it is recommended not to use halogen-containing or halogenated solvents. High-boiling-point solvents, such as DMF, NMP, DMSO, etc., are best used in combination with other low-boiling-point solvents.
[0020] In addition, component A also includes a fluorine-free acidic resin a2, which can be prepared in a similar manner to the fluorine-containing acidic resin a1, such as by a one-step reaction of a fluorine-free alcohol or phenol or a substituted phenol with an acid anhydride. The resin raw material for preparing the fluorine-free acidic resin a2 does not contain fluorine, and the glass transition temperature Tg after curing with the epoxy resin is higher than 150°C. The acid equivalent value V of the acidic resin excluding the solvent is a Greater than 180g / mol. Available fluorine-free alcohols and types are not limited, for example, monohydric, dihydric and polyhydric alcohols, phenol and substituted phenols can be used to react with the aforementioned anhydrides to prepare, including but not limited to methanol, ethanol, cyclohexanol, benzyl alcohol, (meth) hydroxyethyl acrylate, (meth) hydroxypropyl acrylate, ethylene glycol, propylene glycol, butanediol, diethylene glycol, 1,4-cyclohexanediol, terephthalic acid, glycerol, pentaerythritol, phenol, p-methoxyphenol, etc. Acidic resin a2 may contain solvent. In pure fluorine-free acidic resin a2 without solvent, the acid equivalent value is preferably 170-300g / mol, and in component A without solvent, the mass ratio of a2 can be less than 35%, or even zero. Preferably 0-30%.
[0021] The epoxy resin of component B is cross-linked with the carboxyl group of the acidic resin in component A by heat curing, and a coating with excellent dielectric properties and strong adhesion can be obtained, and no small molecules are released during the curing reaction, which is suitable for PCB technology. The epoxy resin suitable for the present invention can be selected from a wide range of options, including fluorine-containing epoxy resins, ordinary fluorine-free bisphenol A type, bisphenol F type, bisphenol S type, phenolic type, biphenyl type, naphthalene skeleton-containing epoxy resins, and heterocyclic, alicyclic, halogen-substituted epoxy resins, difunctional, trifunctional glycidyl ethers, glycidyl esters and other 1-4 functional epoxy compounds. From the angle of mechanical property, improving heat resistance and dielectric property, preferably fluorine-containing epoxy resin, for example the diglycidyl ether type fluorine-containing epoxy resin of phenyl bis-hexafluoro bisphenol isopropyl alcohol, the diglycidyl ether type fluorine-containing epoxy resin of fluorophenyl bis-hexafluoro bisphenol isopropyl alcohol, the diglycidyl ether type fluorine-containing epoxy resin of hexafluoro bisphenol A, and fluorine-free bisphenol A type, bisphenol F type, phenolic type, biphenyl type, naphthalene skeleton type epoxy resin, hydantoin epoxy resin, glycidyl ether type epoxy resin, and their combination.Select suitable fluorine-containing acidic resin and epoxy resin combination, can regulate the density of cross-linked network, modulus, heat resistance and with the adhesion of copper layer etc..The epoxide equivalent weight of epoxy resin can be 70-600g / mol, preferably 80-500g / mol, and molecular weight is between 200-1000, can be 2-functional or 3-functional, even 4-functional epoxy compound, that is, each resin molecule contains 2-4 epoxy functional groups. Within this range, the acidic thermosensitive resin has high reactivity, sufficient crosslinking, and the density, hardness, heat resistance and flatness of the cured product can be taken into account. Preferably, the epoxy resin has a Tg greater than 180°C after curing with the fluorine-containing acidic resin a1. It is easy for technicians in this field to find a suitable combination from the aforementioned fluorine-containing acidic resin a1 and the above-mentioned epoxy resin. The epoxy resin accounts for at least 10% but less than 50% of the weight of each component except the catalyst excluding the solvent, and the preferred epoxy resin has a mass ratio of 15-45% in the pure acidic thermosensitive resin after the solvent is removed. The epoxy equivalent value represents the mass of the epoxy resin corresponding to each mol of epoxy functional group, which can be measured by the hydrochloric acid-acetone method with reference to the standard method of GB / T1677-2008; the glass transition temperature Tg can be measured by a dynamic mechanical property analyzer (DMA) or a thermal analysis method such as a differential scanning calorimeter (DSC).
[0022] For component C, adding low dielectric constant inorganic nanofillers to the acidic thermosensitive resin can improve the dielectric properties, CTE and developability of the material. Low dielectric constant inorganic nanofillers include silicon oxide, nitrogen carbide, boron nitride, mica powder, kaolin, etc. Boron nitride has the lowest dielectric constant Dk (about 1.6), while silicon oxide has a Dk of about 1.6. k It is related to its preparation method. The silica particles produced by gas phase and precipitation method are small, and the original particle size of the particles is in the range of tens of nanometers. kAbout 2.0; silica produced by melting method, with large particle size, D k It has also increased a lot (about 3.9-4.0). The suitable filler particle size is 20-600nm, preferably 20-300nm. Nano fillers have strong aggregation and poor dispersion. Although large-particle fillers are easy to disperse, they will affect the flatness and the appearance of lines or graphics developed by alkaline aqueous solutions. The surface of the fillers can be modified to improve their dispersion state in the resin, which has a great influence on the viscosity and fluidity of the resin composite. Fillers of different chemical compositions and particle sizes can be combined and used in combination. According to the characteristics of the fillers and the specific material performance requirements, suitable fillers and their combinations can be selected, taking into account the D of the coating-metal film / sheet. k , CTE, fluidity and thermal stability of the material. The mass ratio of the nanofiller in the pure acidic thermosensitive resin excluding the solvent is preferably 25%-55%. If the filler is added more, such as more than 60%, it will have an adverse effect on the adhesion and development of the coating and copper. The preferred ratio is 25-50%. Therefore, the relative dielectric constant D of the inorganic nanofiller selected from the component C is k Less than 4, particle size is 20-600nm, preferably 20-300mm.
[0023] The auxiliary agent of component D includes epoxy thermal curing catalyst and other optional auxiliary agents. Among them, adding an appropriate amount of epoxy thermal curing catalyst can improve the activity of thermal curing of acidic resin and epoxy resin, and improve the degree of curing and crosslinking. Known epoxy thermal curing catalysts can be used, such as tertiary amines, tertiary phosphines, boron trifluoride amine complexes, substituted imidazoles, dicyandiamide, dihydrazides, metal complexes, etc. The dosage and characteristics of these catalysts are introduced in special books. The dosage of the catalyst is 0.1-5% of the total mass of AC, preferably 0.2-1%.
[0024] Other additives: Appropriate amounts of other additives may be added to the acid resin compound, including defoamers, leveling agents, colorants, antioxidant stabilizers, etc.
[0025] Solvent: Adding solvent during preparation can adjust the viscosity of the acidic thermosensitive resin, so that each component is fully dissolved and mixed, and it is convenient to coat it on the metal foil. The boiling point of the solvent is 60-180°C, and it is better to use ether solvents at 60-130°C, such as tetrahydrofuran (THF), dipropyl ether, dibutyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether; ketone solvents, such as acetone, butanone, cyclohexanone, etc.; aromatic hydrocarbon solvents, such as toluene and xylene; ester solvents, such as ethanol, isopropanol, butanol, butyl acetate, dimethyl carbonate, dibutyl carbonate, etc. can also be used for short-term use. These solvents can be used alone or in combination, and the amount used is based on the appropriate viscosity of the resin composite, convenient coating and removal.
[0026] A pre-coated resin copper foil comprises a micron-thick conductive metal foil, an acidic heat-sensitive resin coated on the conductive metal foil, and a protective film attached to the acidic heat-sensitive resin for protection. The copper foil can be rolled up, stored at low temperature, and transported.
[0027] Although highly conductive metal materials can be used as conductive metal foil, considering the etching performance, cost and maturity, low loss factor D is preferred. f <0.01, low roughness, high temperature oxidation resistance and high temperature ductility, electronic grade copper foil, preferably 5-30um thick. If the thickness of the conductive metal foil is <10um, a carrier film needs to be added to the lower surface of the copper foil.
[0028] The components of the acidic thermosensitive resin of the present invention are mixed, and a solvent for assisting dissolution is added, and the mixture is stirred evenly to form a fluid, coatable slurry fluid, which is then coated on a copper foil, and the solvent is rapidly evaporated at a temperature of 60-120°C to form a pre-coated resin copper foil. In order to facilitate storage, transportation and use, a carrier film can be added to the bottom of the copper foil, and a protective film is also attached to the upper surface coated with the resin. That is, a uniform, coatable slurry resin composite is first applied to a copper foil carrier, and after the solvent is rapidly evaporated at a temperature of 60-120°C, a protective film and a carrier film are respectively attached to the upper and lower surfaces of the copper foil to form a PCCF with both upper and lower surfaces protected.
[0029] In order to evenly disperse the filler in the resin composition, the filler can be evenly mixed with the liquid components in the composition except the epoxy heat curing catalyst, and the filler-resin mixture can be ground using a forced mixing device, including a grinder, a high-speed disperser, a sand mill, etc. It is preferred to evenly disperse the filler with an acidic resin or an epoxy resin first, and finally add the remaining components to prepare a uniform, coatable slurry resin composite.
[0030] Suitable carrier films and protective films include various transparent or translucent plastic films with certain rigidity and a thickness of 20-100 μm, such as polyester film (PET film), modified PET film (i.e., PETG film), PE film, PP film, PVC film, PMMA film, PO film, etc. As carrier films, PET films and PVC films with a thickness of 20-60 μm are preferred; as protective films, translucent or opaque PE films and PP films with a thickness of 20-80 μm are preferred, and PE films with a thickness of 20-40 μm or stretched oriented PP films are further preferred as protective films.
[0031] The thickness of the coated acidic thermosensitive resin layer after removing the solvent is 8-80 μm, preferably 10-50 μm, to meet the requirements of fine circuits for etching pattern quality and electrical insulation. A variety of coating methods and equipment can be used to coat the uniform slurry resin composite on the carrier copper foil, including coating methods such as scraping, roller coating, slit coating and screen printing.
[0032] The volatile temperature of the solvent added for preparing the acidic thermosensitive resin should be lower than 120℃ to reduce the influence of high temperature on the resin performance. The time for removing the solvent should be controlled within 15 minutes, preferably within 8 minutes. The temperature and time for removing the solvent are related to the selected solvent. The better conditions for removing the solvent are 60-100℃ and within 8 minutes. To accelerate the removal of the solvent, a hot air drying tunnel or a blast oven can be used, or an infrared heating furnace and ventilation can be used. If the coating is relatively thin, such as the dry film thickness within 15mm, under better hot air and temperature conditions, the solvent can be basically removed within 5 minutes, and the residual amount is within 1%.
[0033] The coating can be applied in a single sheet or in a roll-to-roll continuous manner on a coating line. After removing the solvent and applying a protective film, the PCCF can be rolled or cut into sheets of the required size. In order to maintain the best condition, the PCCF should be stored at a relatively low temperature, such as -10 to 10°C and in a dry state away from light.
[0034] The resin-precoated copper foil of the present invention can be used for preparing multi-layer circuit boards.
[0035] Preparation of electronic circuit boards with PCCF: After taking out the low-temperature stored PCCF, place it at room temperature for 2 hours, peel off the PE protective film and symmetrically stick the exposed resin coating on the front and back sides of the core layer substrate, so that the copper foil of the PCCF faces outward. The core inner layer substrate can be a PCB substrate or a copper plate, on which the circuit pattern can be prepared in advance. PCCF can be laminated using a laminating machine at 60-90°C under heating and a laminating pressure of 0.2-1MPa; it can also be laminated using a vacuum laminating machine. Those skilled in the art can refer to the known processes to implement it.
[0036] Etching and developing: Use PCB technology to etch the circuit pattern on the copper foil and expose the resin layer. At the location where the perforation pattern needs to be made, rinse with alkaline water to dissolve the acidic resin layer, forming a hole pattern corresponding to the holes on the surface copper foil. The size and shape of the holes are related to the aperture and shape of the copper foil bonded thereon and chemically etched. After rinsing with pure water to remove the developer (alkaline water) and the etched resin and filler, use 100℃ hot air to dry the water, and then put it in an environment of 180-220℃ for heat treatment for 30-90 minutes. Then you can repeat the steps of bonding PCCF, etching copper foil and resin layer, and heat treatment to make multi-layer stacking. In the preparation process of multi-layer stacking, the interlayer through hole needs to be copper-plated at the position of the connection. After copper plating at the opening using the method known in the PCB industry, the next layer of PCCF is bonded for stacking. Repeating this process, you can prepare a multi-layer PCB board with fine circuits and through holes. This process does not require the use of mechanical drilling or laser ablation to make through holes, and chemical etching can batch process the through holes on the entire surface at one time, and can prepare sub-micron and micron-sized conductive holes, which is extremely advanced.
[0037] Alkaline developers include hydroxides or weak acid salts of alkali metals, such as sodium hydroxide, potassium hydroxide, sodium bicarbonate, and sodium carbonate, which are usually prepared into aqueous solutions with a mass concentration of less than 3%, and in most cases 1-2%. Aqueous solutions of organic bases can also be used, such as aqueous solutions of tetramethylammonium hydroxide. Surfactants and a small amount of water-soluble organic solvents can also be added to the developer. The pH value of the alkaline developer is greater than 9, usually in the range of 9-12. Development methods include immersion, vibration, spraying and other methods, and reference can be made to the developer, development equipment and process conditions commonly used in this industry.
[0038] Thermal curing: The PCCF-bonded samples need to be thermally cured after etching to allow thermal crosslinking inside the patterned resin to generate a dielectric insulation layer with excellent performance. The samples should be washed with deionized water before thermal treatment. Thermal curing is mainly to cure epoxy resin, and the curing temperature can be 150-220°C and the time can be 30-90 minutes; depending on the composition of the resin composite, it can be preferably 170-190°C and the time can be 30-70 minutes. Suitable curing reaction conditions can be determined by infrared spectroscopy and the mechanical properties of the cured product. Those skilled in the art can refer to similar thermal curing conditions and processes for PCB boards.
[0039] The resin-coated copper foil prepared by the present invention has a peeling force of the resin coating on the copper foil greater than 5N / 25mm; the resin coating on the resin-coated copper foil can be etched with holes or micrometer patterns by an alkaline aqueous solution, and the D k <3.5, D f <0.02, CTE<40ppm. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is the H-NMR spectrum of phenyl bis(hexafluorobisphenol) isopropanol;
[0041] Figure 2 This is the H-NMR spectrum of fluorophenyl bis(hexafluorobisphenol) isopropanol. DETAILED DESCRIPTION
[0042] In order to allow those skilled in the art to understand the present invention more clearly and intuitively, the present invention will be further described below.
[0043] Example
[0044] An acidic heat-sensitive resin comprises the following components:
[0045] A: acidic resin, 15-60 parts by weight, preferably 20-50 parts by weight;
[0046] B: epoxy resin, 10-50 parts by weight, preferably 15-45 parts by weight;
[0047] C: inorganic nanofiller, 25-55 parts by weight, preferably 30-50 parts by weight;
[0048] The total weight of components AC is 100 parts by weight;
[0049] In addition, it also includes D: auxiliary agent, which includes epoxy thermal curing catalyst, and the amount of the epoxy thermal curing catalyst is 0.1-5%, preferably 0.2-1% of the total weight of components AC.
[0050] raw material:
[0051] Fluorine-containing acidic resin: The acidic resin of component A is a fluorine-containing acidic resin, which is prepared by reacting the following fluorine-containing diol with anhydride. Hexafluorobisphenol A (FA) is a commercially available product, phenyl bis(hexafluorobisphenol isopropanol) (FB) and fluorophenyl bis(hexafluorobisphenol isopropanol) (F-FB) are prepared by the Polymer College of Sichuan University. In Table 1, FB is a mixture of two isomers of 1,3- and 1,4-disubstituted, FBm / FBp=9 / 1. The structural characterization of FB and F-FB is shown in Figure 1 and Figure 2 .
[0052]
[0053] Table 1 Fluorine content (mass ratio w%) and acid equivalent value (g / mol) of fluorinated alcohols and their acidic resins
[0054]
[0055] The following synthesis examples are all measured in parts by mass or mass %, and the acid anhydrides used are all commercial reagents.
[0056] Resin Synthesis Example 1: 168 parts of fluorine-containing alcohol FA, 1 part of pyridine, 100 parts of butanone and 168 parts of methyltetrahydrophthalic anhydride (MTPA) were added to a flask equipped with a thermometer, a mechanical stirrer and a condenser, and the stirring was turned on. The reaction was carried out at 70-100° C. for 10 hours to obtain a fluorine-containing acidic resin. The acid equivalent value of the pure resin after solvent removal was 330 g / mol, and the non-volatile content was 73%, which is hereinafter referred to as FA-A1 resin.
[0057] Resin Synthesis Example 2: Similarly, 205 parts of fluorine-containing alcohol FB, 1 part of pyridine, 150 parts of butanone and 195 parts of trimellitic anhydride were reacted under the method and conditions as in Resin Synthesis Example 1 to obtain a fluorine-containing acidic resin. The acid equivalent value of the pure resin was 195 g / mol, and it was recorded as FB-A1 resin.
[0058] Resin Synthesis Example 3: Similarly, 215 parts of fluorophenyl fluorinated alcohol F-FB, 1 part of pyridine, 150 parts of butanone, 75 parts of phthalic anhydride and 96 parts of trimellitic anhydride were reacted under the method and conditions as in Resin Synthesis Example 1 to obtain a fluorine-containing acidic resin with an acid equivalent value of 250 g / mol for the pure resin, which was recorded as F-FB-A1 resin.
[0059] Resin Synthesis Example 4: Use 72 parts of 1,4-dihydroxymethylcyclohexane, 1 part of pyridine, 100 parts of butanone, 75 parts of phthalic anhydride and 96 parts of trimellitic anhydride to react under the same method and conditions as Resin Synthesis Example 1 to obtain acidic resin A2. The acid equivalent value of the pure resin is 160 g / mol, recorded as HC-A2 resin.
[0060] Filler: Filler 1, SiO2, precipitated SiO2 commercially available from Suzhou Beike Nanotechnology Co., Ltd., with a particle size of 25-50 nm; Filler 2, nano-silicon oxide low dielectric powder commercially available from Yuanjie New Materials Technology (Zhejiang) Co., Ltd., with a particle size of 400-600 μm and a dielectric constant ≤2.9.
[0061] Epoxy resin: Zhuhai Shengquan High-tech Materials Co., Ltd. sells diglycidyl ether of hexafluorobisphenol A type fluorinated epoxy resin, novolac epoxy resin and bisphenol A type epoxy resin on the market, and their epoxy values are 330g / mol, 195g / mol and 200g / mol respectively.
[0062] Description of implementation method
[0063] Sample preparation: The compositions of the acidic thermosensitive resins of Examples 1-4 of the present invention and Comparative Examples 1-2 are shown in Table 2. Each component in Table 2 is further added with a catalyst phenylimidazole whose mass ratio is 1% of the total mass of the acidic thermosensitive resin, and the quantity is the net mass part without solvent. After adding each component according to Table 2 and roughly mixing, stir and disperse it into a uniform slurry with a high-speed mixing equipment. Use a slit coater to apply the slurry to a 10μm copper foil, blow hot air at 90°C for 8 minutes to remove the solvent, and stick a 30μm PE film and a 30μm PET film on the upper and lower sides of the copper foil, respectively, to obtain a pre-coated resin copper foil sample, which is stored in a refrigerator below 0°C.
[0064] Etching and evaluation: Take out the pre-coated resin copper foil stored in the refrigerator and place it at room temperature for 1 hour. Remove the PE protective film on one side of the resin layer and stick it to a 0.3mm thick copper plate. Put it into a vacuum laminating machine. The laminating conditions are 80℃ and 0.6MPa. After taking it out, remove the PET protective film on the bottom layer of the copper foil, stick the PCB photoresist film and film, expose it with a LED parallel light source with a wavelength of 365nm, spray it with a 1% mass concentration of Na2CO3 aqueous solution at 0.2MPa for 2-3 minutes, rinse with deionized water, and then check it with a digital microscope. If a circular hole with a diameter of 50um can be etched, it is marked as √, otherwise it is marked as ×.
[0065] Physical property measurement and evaluation:
[0066] The samples used for physical property testing were etched and rinsed as above, placed in a 100°C forced air oven for 10 minutes, and then heat treated in a 200°C oven for about 90 minutes. The samples were tested for storage modulus E at room temperature using a dynamic mechanical properties tester (DMA), with a heating rate of 10°C / min. Tg greater than 200°C was marked as √, otherwise it was marked as ×; storage modulus E greater than 4.2GPa was marked as √, otherwise it was marked as ×. The dielectric properties of the samples at room temperature and in the range of 100Hz-5MHz were tested using a Concept 50 broadband dielectric relaxation spectrometer, and the dielectric constant D at 1MHz was recorded. k , the dielectric loss is less than 0.02 marked as √, otherwise marked as ×. The electrical insulation is tested by Beijing Guance Precision Instrument Equipment DDJ-50KV type voltage withstand breakdown tester, and the insulation resistance is greater than 1x10 13 Ω is marked as √, otherwise it is marked as ×. For the samples of adhesion and heat resistance evaluation of the cured resin layer, copper plate and copper foil, the pre-coated resin copper foil with the upper and lower protective films removed is cut into 70×50mm strips, placed in a 100℃ blast oven for 10 minutes, and then heat treated in a 200℃ oven for about 90 minutes. Float the sample on a 288℃ tin bath with the resin surface facing upwards to observe whether the resin layer peels off or bubbles. If there is no abnormal phenomenon such as peeling or bubbling, it is marked as qualified for adhesion and heat resistance and marked as √; if there is abnormal phenomenon such as peeling, falling off or bubbling, it is marked as unqualified and marked as ×.
[0067] Table 2 also shows exemplary effects of the present invention.
[0068] The results of Examples 1-4 show that by using a fluorine-containing acidic resin and a low-refractive-index nanofiller in combination with a fluorine-containing epoxy resin, a resin cured layer with a high filler content can also obtain a dielectric constant lower than 3.5 and a CTE of about 40 ppm; therefore, by reasonably matching the fluorine-containing acidic resin with the epoxy resin and the filler, the cured resin can take into account dielectric properties, CTE, heat resistance, and mechanical and insulation properties, and can meet the requirements of electronic circuit boards for dielectric materials. Comparative Example 1 uses a non-fluorine-containing acidic resin curing agent and an ordinary epoxy resin, and the dielectric constant D k Comparative Example 2 uses fluorine-containing resin but does not add filler, and the CTE of the cured product under the same conditions is very high. The performance of both comparative examples is inferior to that of the embodiment, and they are not suitable as dielectric insulating materials for high-frequency electronic circuits.
[0069] Table 2. Composition and properties of photosensitive dielectric insulating films
[0070]
[0071] Note: Each component in the table is added with 1w% of catalyst phenylimidazole.
[0072] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the scope of protection of the present invention.
Claims
1. An acidic heat-sensitive resin, characterized in that: The components include: A: acidic resin, 15-60 parts by weight; B: epoxy resin, 10-50 parts by weight; C: low dielectric constant inorganic nanofiller, 25-55 parts by weight; The total weight of components AC is 100 parts by weight; In addition, it also includes D: an auxiliary agent, wherein the auxiliary agent includes an epoxy thermal curing catalyst, and the amount of the epoxy thermal curing catalyst is 0.1-5% of the total weight of components AC; The acidic resin includes a fluorine-containing acidic resin prepared from a fluorine-containing alcohol or a fluorine-containing phenol having a fluorine mass ratio greater than 30% as a raw material; It is prepared using fluorinated alcohol or fluorinated phenol represented by FA, F-FB, FBm, FBp as raw materials; Acidic resins are obtained by the reaction of fluorinated alcohols / phenols with acid anhydrides; The acid anhydride is selected from one or more of the aromatic or aliphatic acid anhydrides of phthalic anhydride, (methyl)tetrahydrophthalic anhydride, (methyl)hexahydrophthalic anhydride, (methyl)dihydrophthalic anhydride, maleic anhydride, itaconic anhydride, succinic anhydride, trimellitic anhydride, pyromellitic dianhydride, diphenyl ether tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, succinic anhydride, and cyclohexyl tetracarboxylic dianhydride.
2. An acidic heat-sensitive resin as claimed in claim 1, characterized in that: The components include: A: acidic resin, 20-50 parts by weight; B: epoxy resin, 15-45 parts by weight; C: inorganic nanofiller with low dielectric constant, 30-50 parts by weight; The total weight of components AC is 100 parts by weight; In addition, the epoxy thermal curing catalyst is used in an amount of 0.5-1% of the total weight of components AC.
3. An acidic thermosensitive resin as claimed in claim 1, characterized in that: In the solvent-free component A, the acid equivalent value V of the acidic resin is a The mass ratio of fluorine in component A is greater than 20%.
4. An acidic heat-sensitive resin as claimed in claim 3, characterized in that: The acidic unsaturated resin also includes a fluorine-free acidic resin accounting for 0-35% by weight of component A, which is prepared by a one-step reaction of a fluorine-free alcohol, phenol or substituted phenol and an acid anhydride; The acid anhydride is selected from one or more of the aromatic or aliphatic anhydrides of phthalic anhydride, (methyl)tetrahydrophthalic anhydride, (methyl)hexahydrophthalic anhydride, (methyl)dihydrophthalic anhydride, maleic anhydride, itaconic anhydride, succinic anhydride, trimellitic anhydride, pyromellitic dianhydride, diphenyl ether tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, succinic tetracarboxylic dianhydride, and cyclohexyl tetracarboxylic dianhydride; The glass transition temperature Tg of the non-fluorinated acidic resin after curing with the epoxy resin is higher than 150°C, and the acid equivalent value V of the acidic resin without taking into account the solvent a It is 170-300g / mol.
5. An acidic heat-sensitive resin as claimed in claim 1, characterized in that: The epoxy resin in component B includes fluorine-containing epoxy resin and / or fluorine-free epoxy resin. The fluorine-containing epoxy resin includes diglycidyl ether type fluorine-containing epoxy resin of phenyl bis(hexafluorobisphenol isopropanol), diglycidyl ether type fluorine-containing epoxy resin of fluorophenyl bis(hexafluorobisphenol isopropanol), and diglycidyl ether type fluorine-containing epoxy resin of hexafluorobisphenol A. The fluorine-free epoxy resin includes bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac type epoxy resin, biphenyl type epoxy resin, naphthalene skeleton type epoxy resin, hydantoin epoxy resin, and glycidyl ether type epoxy resin. The epoxy equivalent value of the epoxy resin is between 70-600 g / mol and the molecular weight is between 200-1000.
6. An acidic heat-sensitive resin as claimed in claim 5, characterized in that: The epoxy equivalent value of epoxy resin is between 80-500 g / mol.
7. An acidic heat-sensitive resin as claimed in claim 5, characterized in that: In the component C, the inorganic nanofiller with low dielectric constant is selected from the group consisting of inorganic nanofillers with relative dielectric constant D k Silicon nitride, nitrogen carbide, boron nitride, mica powder, kaolin with a content less than 4; The particle size of the low dielectric constant inorganic nanofiller is 20 to 600 nm.
8. An acidic heat-sensitive resin as claimed in claim 7, characterized in that: The particle size of the low dielectric constant inorganic nanofiller is 20-300 nm.
9. An acidic heat-sensitive resin as claimed in claim 7, characterized in that: In the component D, the epoxy thermal curing catalyst is selected from tertiary amines, tertiary phosphines, boron trifluoride amine complexes, phenylimidazole, dicyandiamide, dihydrazides, and metal complex catalysts.
10. A resin pre-coated copper foil, characterized in that: It comprises a conductive metal foil, a layer of the acidic heat-sensitive resin as claimed in any one of claims 1 to 9 coated on the conductive metal foil, and a protective film attached to the acidic heat-sensitive resin for protection; The thickness of the conductive metal foil is 5-30 μm; if the thickness of the conductive metal foil is less than 10 μm, a carrier film is also attached to the lower surface of the copper foil; The carrier film is a PET film or a PVC film with a thickness of 20-60 μm; The protective film is a translucent or opaque PE film or PP film with a thickness of 20-80 μm; The thickness of the acidic thermosensitive resin layer is 8-80 μm.
11. The resin-precoated copper foil according to claim 10, characterized in that: The thickness of the acidic thermosensitive resin layer is controlled to be 10-50 μm.
12. The method for preparing the resin-precoated copper foil according to claim 10, comprising the following steps: Mix the components of the acidic thermosensitive resin, add a solvent to assist in dissolving, stir evenly to form a fluid, coatable slurry, apply it to the conductive metal foil, and quickly evaporate the solvent at a temperature of 60-120°C to form a pre-coated resin copper foil; The solvent is selected from one or more of tetrahydrofuran, dipropyl ether, dibutyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, acetone, butanone, cyclohexanone, toluene, xylene, ethanol, isopropanol, butanol, butyl acetate, dimethyl carbonate, and dibutyl carbonate.
